IMOVE: A Motion Tracking and Projection Framework for Social Interaction Applications. (3rd March 2019) - Kegeleers, Marie; Bruens, Raoul; Liefaard, Maxim; Salamon, Nestor Z.; Bidarra, Rafael
Abstract : In public places such as malls, train stations, and airports, there is a constant flow of people either waiting or commuting. Even though people at these locations are surrounded by many other individuals, mostly there is little social interaction, which generally creates a gloomy atmosphere. Any applications promoting social interactions are a welcome addition. We present IMOVE, an interactive framework aimed at facilitating the development of such applications. It offers a combination of motion tracking and projection methods which makes it easier to create interactive experiences and games, tailored to motivate people to move around, explore, and, most importantly, interact with each other in a fun way. People moving around trigger events and effects, interacting with the applications using their body movements or even collaboratively working towards an outcome. IMOVE was validated by means of a variety of applications in a real scenario, the entrance hall of a busy public building: the classic Pong game, a collaborative and accessible casual game ( Save the Turtles! ), and a procedural visual art generator based on game mechanics ( Light Trails ). All applications have been successfully running for the past year. The IMOVE framework is freely available online and it has been shown to be particularly suited and accessible to novice game and interactive application developers for large public spaces.